Video Capsule Endoscopy: A Tool for the Assessment of Small Bowel Transit Time - Hejazi, Reza A.; Bashashati, Mohammad; Saadi, Mohammed; Mulla, Zuber D.; Sarosiek, Irene; McCallum, Richard W.; Zuckerman, Marc J. (Frontiers in Medicine, 2016)
Purpose: Video capsule endoscopy (VCE) is a procedure that uses a wireless camera to take pictures of the gastrointestinal tract. A wireless motility capsule (WMC) of a similar size has been developed, which measures pH, pressure, and temperature, and can be used to assess regional and total gastrointestinal transit times. VCE could also potentially be used as a tool for measuring small bowel transit time (SBTT). Methods: This study was designed to obtain SBTT from VCE and compare it with historical data generated by WMC. Gastric transit time (GTT) was also measured. Patients were included if the indication for VCE was either iron deficiency anemia (IDA) or overt obscure GI bleed (OOGIB) and they did not have any known motility disorder. Results from VCE were also compared in diabetic versus non-diabetic patients. Results: There were a total of 147 VCE studies performed, including 42 for OOGIB and 105 for IDA. Median GTT and SBTT were 0.3 and 3.6 hours, respectively. The overall median GTT and SBTT were 0.3 and 3.6 hours, respectively, in the IDA group compared with 0.3 and 3.4 hours in the OOGIB group. When compared with WMC, the GTT and SBTT were significantly faster in both groups (GTT: 3.6 hours and SBTT: 4.6 hours). The median GTT and SBTT were not significantly different in diabetics versus non-diabetics: (GTT: 17.5 vs. 18.0 minutes (P=0.86) and SBTT: 3.9 hours (237 minutes) vs. 3.8 hours (230 minutes), respectively (P=0.90). Conclusion: SBTT as measured using VCE is not significantly different in OOGIB compared with IDA. Both GTT and SBTT are significantly faster as assessed by VCE, which is initiated in the fasting state, compared with WMC measurement, which is initiated after a standard meal. In summary, VCE could potentially be used for measuring SBTT in the fasting state.